2022
DOI: 10.1002/adfm.202209100
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Tube‐Based Volume Effect Triboelectric Nanogenerator with Salt and pH Sensitivity

Abstract: Due to the advantages of natural softness and flexibility of water, liquid–solid‐based triboelectric nanogenerators (TENGs) have aroused wide attention recently and much effort has been devoted to improving its output performance. Herein, the performance of liquid–solid‐based TENG is greatly improved through two simple steps. First, an end electrode is added into the traditional tube‐based TENG and the volume effect is successfully realized, with the output voltage improved by ≈40 times to 240 V. Then, the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Shortly after, the ultrahigh peak power density of 1910 W m −3 and average power density of 459 W m −3 was realized by a liquid‐solid TENG with solution‐tube‐based structure through the volume effect and solution optimization. [ 37 ] Jurado et al. researched the effect of water‐dielectric interfaces on the output performance of single electrode liquid‐solid TENG for wave energy harvesting.…”
Section: Ocean Energy Harvestingmentioning
confidence: 99%
See 3 more Smart Citations
“…Shortly after, the ultrahigh peak power density of 1910 W m −3 and average power density of 459 W m −3 was realized by a liquid‐solid TENG with solution‐tube‐based structure through the volume effect and solution optimization. [ 37 ] Jurado et al. researched the effect of water‐dielectric interfaces on the output performance of single electrode liquid‐solid TENG for wave energy harvesting.…”
Section: Ocean Energy Harvestingmentioning
confidence: 99%
“…it can be used for the detection of high precision PH and salinity. [ 37 ] To monitor the related corrosion state of Mg treated by micro‐arc oxidation (MAO), Mg‐based sheets and polydimethylsiloxane film were used as triboelectric materials to fabricate an Mg‐based TENG (Figure 16b). [ 183 ] Experimental results show a linear relationship in simulated body fluid immersion tests and indicated that TENG sensor can successfully monitor the corrosion of MAO‐Mg.…”
Section: Ocean Sensing and Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods can avoid the problems of fully enclosed TENGs for water wave energy harvesting, but the output performance is still relatively low now. [24,29,31,32] In this work, a novel liquid-solid TENG with an asymmetric conuration was designed and fabricated to improve the capability of water wave energy harvesting. This TENG is based on the opposite dynamic EDLs and adopts a new working scheme, which is an innovation compared to previous fully enclosed TENGs and liquid-solid TENGs.…”
Section: Introductionmentioning
confidence: 99%